Autism-associated Scn2a haploinsufficiency disrupts in vivo dendritic signaling and impairs flexible decision-making - Hao Wu; Luqun Shen; Jonathan Indajang; Neil K. Savalia; Timothy G. Johnson; Jiayin Qu; Kevin J. Bender; Alex C. Kwan (Proceedings of the National Academy of Sciences, 2025)
SCN2A is a high-confidence risk gene for autism spectrum disorder. Loss-of-function mutations in Scn2a reduce dendritic excitability in neocortical pyramidal cells. However, the impact of Scn2a haploinsufficiency on dendritic signaling in vivo, particularly during behavior, is unknown. In this study, we used two-photon microscopy to image dendritic calcium transients in deep layer pyramidal cells in the mouse medial frontal cortex. Scn2a +/− mice had diminished coupling between apical and proximal dendritic compartments. Pyramidal tract neurons had abnormal event rates, while intratelencephalic neurons had compartment-specific alterations indicative of diminished dendritic integration. In a matching pennies task, Scn2a +/− mice were inflexible in the face of changing competitive pressure. Apical dendritic tuft in intratelencephalic neurons typically encoded reward and strategy, but these task-specific representations were altered in Scn2a +/− mice. Collectively, the findings demonstrate that Scn2a haploinsufficiency weakens dendritic integration in vivo and disrupts dendritic encoding of task variables during flexible decision-making.